Transcription activation depends on the length of the RNA polymerase II C‐terminal domain - Sawicka, Anna (EMBO J, 2021)
Eukaryotic RNA polymerase II (Pol II) contains a tail‐like, intrinsically disordered carboxy‐terminal domain (CTD) comprised of heptad‐repeats, that functions in coordination of the transcription cycle and in coupling transcription to co‐transcriptional processes. The CTD repeat number varies between species and generally increases with genome size, but the reasons for this are unclear. Here, we show that shortening the CTD in human cells to half of its length does not generally change pre‐mRNA synthesis or processing in cells. However, CTD shortening decreases the duration of promoter‐proximal Pol II pausing, alters transcription of putative enhancer elements, and delays transcription activation after stimulation of the MAP kinase pathway. We suggest that a long CTD is required for efficient enhancer‐dependent recruitment of Pol II to target genes for their rapid activation.